(untitled) (INDIAN JOURNAL OF VOCATIONAL EDUCATION, 2023)
Assessment at regular intervals in Make in India Initiatives is to create trained manpower in School/ Training center and to prepare student for world of work, school/ center is a very important aspect. Various commissions and committees have expressed their concern about the traditional approach of evaluation system. There is urgent need to resolve questions as what evaluation strategy should be adopted for vocational courses to keep such thing in mind present study have been taken. In this study rubrics were developed for class 9" students of Automobile Technology, NSQF level 1 (L1). Four schools were identified for pilot tryout in Himachal Pradesh and Haryana. An attempt was made to evaluate the student’s performance by using developed Rubrics (Criteria Based Assessment). Guidelines were also made for better implementation of the project. In pilot tryout, it was observed that rubric based assessment helped student to improve their learning, It is strongly recommended to introduce rubrics-based Assessment in Academic. Vocational courses should be assessed by this relatively new concept, Rubric Based Assessment.